Persistent vomiting, an alarm sign in children - G., Ramya; A., Arul Kumaran; Gupta, Tanay (International Journal of Contemporary Pediatrics, 2020)
Brain tumors, the second common cancer following hematological malignancies account for up to 21% of all malignancies below 14 years of age. Medulloblastoma is a common form of Primitive neuro ectodermal tumor and likely arise from either the external granular layer (e.g., desmoplastic variant) or the subependymal matrix cells of the fourth ventricle (e.g., classic variant), or both. The clinical course of the disease is aggressive in children than in adults. The tumor can invade the CSF through the ventricles or even cause metastases to bones and lymph node. With the emergence of advanced technologies and treatment facilities, the morbidity and mortality of the disease is greatly improved with a five-year survival of up to 75%. However, the presence of disease in children <3 years or evidence of dissemination on diagnosis carries poor prognosis. Here we are discussing a case of 5-year-old girl who presented to OPD with vomiting for 1 month.